The Effect of Job Rotation on Ship Crew Job Satisfaction at PT Samudera Indonesia Ship Management - Fancy Awaliyatul Luluil Mubarokah Zaey; Vidya Selasdini; M Nurdin; Purnomo Purnomo (Greenation International Journal of Economics and Accounting, 2023)
PT Samudera Indonesia Ship Management (SISM) was established in 1991 to support shipping activities by providing professional, efficient and added value in the form of competitive advantage or customers. SISM is a merger of several ship management divisions in various shipping business units in Samudera Indonesia. SISM is also supported by highly competent people and a team of expertise to operate ships safely and to meet national and international requirements according to market needs, as well as best practices in ship management. Based on the data, the problems that exist discuss the job rotation that is not in accordance with the job satisfaction of the crew at PT Samudera Indonesia Ship Management. The purpose of this study is to determine and analyze how much influence job rotation has on job satisfaction of ship crews. In this study found the results of the data from the effect of job rotation on the job satisfaction of the crew of the ship. For this shipping company, it is necessary to pay more attention to the things that encourage the creation of good job satisfaction, the shipping company must run a good crew and be ready to meet the existing fleet within the shipping company itself.